Oral Health Knowledge and Habits of Hungarian Monozygotic and Dizygotic Twins: A Pilot Study - Klaudia Liptak; Laura Liptak; Noemi Katinka Rozsa; Peter Hermann; Adam Domonkos Tarnoki; David Laszlo Tarnoki; Daniel Vegh (Elsevier, 2024)
ABSTRACT: Objective: The aim of this research was to collate and analyse the data on the oral health knowledge and the related habits of a Hungarian cohort of monozygotic (MZ) and dizygotic (DZ) twins using the newly developed World Health Organisation Oral Health Questionnaire for Adults (Annex 7). Method: A total of 15 sets of MZ twins and 14 sets of DZ twins (58 individuals) aged between 18 and 71 years were enrolled in the study. Each participant had to fill out a web-based questionnaire which comprised 23 questions (Google Forms). The data were collated and the oral health/hygiene habits of MZ and DZ twins were compared. Results: No significant differences were detected between MZ and DZ twins with regards to their daily tooth-cleaning habits or the tooth-cleaning products used by the 2 groups. For instance, when asked how often they clean their teeth, 80% of MZ twins and 71% of DZ twins responded similarly. Further, both groups provided similar responses when questioned about the use of fluoride toothpaste, frequency of dental visits, and dental counselling received as well as a number of other parameters such as snacking of sweets and fear of visiting dentists. Conclusions: Our pilot analysis of the questionnaire responses from MZ and DZ twins in Hungary did not indicate any significant differences in their oral care habits in general. Further studies with a large cohort are required to confirm or refute our findings.